ETUDE DE LA SENSIBILITE DE QUELQUES PLANTES MARAICHERES A PHOMA SABDARIFFAE ET A SES PRODUCTIONS TOXIQUES AU GABON - Lepengue, Alexis Nicaise; Yala, Jean Fabrice; Ibrahim, B.; Souza, Alain; M’batchi, Bertrand (European Scientific Journal, ESJ, 2013)
Phoma sabdariffae is the main pathogenic fungus agent of roselle in Gabon. This fungus affects plants by producing toxic compounds. The present work was undertaken in order to study the sensitivity of other vegetables to this fungus and its toxins. The susceptibility of 11 plants, which were cultivated for 40 days in a greenhouse, was also tested by measuring infection indices (i) and electrolytes release (le) rate. Results showed that, beside the roselle, all other plants are not sensitive to Phoma sabdariffae. In fact, no wet rot nor shape reduction was noticed in tested plants. However, all 11 vegetables were sensitive to this fungus culture filtrate, with electrolytes release rate superior to 90%. It then appears that Phoma sabdariffae is strictly linked to the roselle, while all its toxic excretions are not host specific, with a broad spectrum activity on other plants.